Puisi Melayu Era Digital: Rekonstruksi Sinematik Berbasis Artificial Intelligence dalam Pembelajaran Apresiasi Puisi - Wiko Antoni; Yusrizal Yusrizal; Elfa Eriyani (Jurnal Riset Rumpun Ilmu Bahasa, 2026)
The rapid advancement of digital technology has created new opportunities for transforming literary works from conventional textual forms into multimodal formats that integrate visual, audio, and interactive elements. This study examines the implementation of the Cinematic Reconstruction Method (CRM) in teaching the appreciation of Malay poetry through Artificial Intelligence (AI). The method facilitates the reconstruction of poetry into cinematic representations while preserving the aesthetic values and cultural meanings embedded in the original text. This research employed an applied research approach involving students from Class A and Class B of the Indonesian Language and Literature Education Study Program at Universitas Merangin. The theoretical framework integrates the concepts of literary reconstruction, multimodal learning, and digital humanities. The findings indicate that the AI-based cinematic approach has significant potential to enhance students' literary literacy, digital creativity, and cultural interpretation skills in the appreciation of Malay poetry.description of the research background, objectives, methods, findings, and implications.